Reply to the comment on: “Dalbavancin for infective endocarditis: a systematic review of effectiveness, safety, and dosing” - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Dalbavancin for infective endocarditis: A systematic review of effectiveness, safety, and dosing - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Infective endocarditis (IE) requires prolonged intravenous antibiotic therapy, leading to extended hospitalization and increased morbidity. Dalbavancin, a long-acting antibiotic with excellent tissue penetration and a favorable safety profile, can be a promising alternative. This systematic review aimed to investigate the current literature regarding the use of dalbavancin for infective endocarditis. Methods A systematic search of PubMed and Scopus was conducted according to PRISMA guidelines. Eligible studies included adult patients (≥ 18 years) with IE diagnosed by the modified Duke criteria, treated with dalbavancin as monotherapy or sequential/consolidation therapy. Data extraction included demographics, type of IE, causative pathogen, dosing regimen, surgical intervention, adverse events, and outcomes. Descriptive analyses were performed. Results Thirty-eight studies including 565 patients were analyzed. The overall cure rate was 88.0%, with a similar success rate across native valve (90.1%), prosthetic valve (90.0%), and cardiac device-related IE (86.0%). Staphylococcus aureus , Coagulase-negative staphylococci (CNS), Streptococcus spp ., and Enterococcus faecalis were the most common pathogens. Cure rates were comparable among most pathogens, though a lower cure rate was evident in infections due to Enterococcus faecalis compared to Streptococcus spp. (80.7% vs. 96.6%, p = 0.008). An effective antimicrobial exposure of 2 weeks had similar success rate compared to a longer period of effective antimicrobial exposure ( p = 0.31). Adverse events were rare (2.9%), with mild rash being the most common. Conclusions Dalbavancin demonstrates high cure rates and excellent tolerability in IE, and could offer an attractive alternative to conventional prolonged intravenous therapy. Further randomized controlled trials are warranted to define standardized protocols.

Similar incidence of S. aureus infection in diabetic patients with and without nasal colonisation - Marina N. Plataki; Petros Ioannou; Stamatis Karakonstantis; Charalampos Bikis; Sofia Maraki; George Samonis; Diamantis P. Kofteridis (Infectious Diseases, 2021)

Treatment pattern, prognostic factors, and outcome in patients with infection due to pan-drug-resistant gram-negative bacteria - Diamantis P. Kofteridis; Angeliki M. Andrianaki; Sofia Maraki; Anna Mathioudaki; Marina Plataki; Christina Alexopoulou; Petros Ioannou; George Samonis; Antonis Valachis (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Hospital-wide antifungal prescription in Greek hospitals: a multicenter repeated point-prevalence study - Matthaios Papadimitriou-Olivgeris; Angeliki M. Andrianaki; Markos Marangos; Nikolaos Sipsas; Eirini A. Apostolidi; Efstratios Maltezos; Periklis Panagopoulos; Dimitris Karapiperis; Kostoula Arvaniti; Eleni-Isidora Perdikouri; George Samonis; Diamantis P. Kofteridis (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Resistance phenotypes and susceptibility of contemporary Serratia isolates in the university hospital of Crete, Greece - George Samonis; Konstantinos Z. Vardakas; Sofia Maraki; Petroula Stamouli; Viktoria-Eirini Mavromanolaki; Diamantis P. Kofteridis; Matthew E. Falagas (Infectious Diseases, 2017)

Factors Influencing Non-albicans Candidemia: A Case–Case–Control Study - Diamantis P. Kofteridis; Antonis Valachis; Dimitra Dimopoulou; Angeliki M. Andrianaki; Athanasia Christidou; Sofia Maraki; Nikolaos A. Spernovasilis; George Samonis (Mycopathologia, 2017)

In vitro susceptibility and resistance phenotypes in contemporary Citrobacter isolates in a University Hospital in Crete, Greece - Sofia Maraki; Konstantinos Z. Vardakas; Viktoria-Eirini Mavromanolaki; Margarita Kyriakidou; George Spais; Diamantis P. Kofteridis; George Samonis; Matthew E. Falagas (Infectious Diseases, 2017)